RESERVATION SYSTEM ADMINISTRATION ORI'EN BREAD IN BREAD USING MICROSOFT ACCESS 2000 - Hartati Hartati; Rahayu Noveandini, SKom, MM (Jurnal Sistem Informasi, 2005)
This scientific writing system consists of the sale of bread on the Oriental. Thissystem is designed to simplify the Oriental in serving customers as long as themanual system is used are considered less efficient and effective. Authors move frommanual systems to computerized systems. Language program used is MicrosoftAccess 2000.With the new system is expected to errors in entering data can be reduced, in makingthe report is done effectively and efficiently as required, so as to improve the qualityof services at a bread company.